(3GdebGdI GdaGVdjIs - (3ehSi Hf ejehf Hf jhSa Hf ESMGb, CHhYeQGf GdbQWHj,J (B601 (3g` s ((3jhMfG Hf EdjGS Hf EHQGgje GdeJWHH GdeSjMi s)
(3ChdgG (B:s
(3bO TgQ ai CYUGQfG hai EbdjefG gPG Hd ai YOI CbGdje SjQI ehdGfG GdbGVi , NdO Gddg CjGeg hfMf fQi Cf fVY ebGdg UZjQI GdMLe LjOI GddaX LGeYI deG CjHGOQHg GdedShY ef GdJOHjQ s
(3BNQgG (B:s
(3hgPG GdbOQ cGa HMSH eG CeQ Hg GdSjO GdCLd GdbGVi GdaGVd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B242 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(5/889) s
Keywords: (3GdWHs